Использование межвидовой гибридизации при cоздании ценного исходного материала льна масличного - Полякова, И.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. Growing flax in Ukraine has a constant growth dynamics. Diversity of growing areas stipulates the creation of varieties with higher plasticity and resistance. In this regard, involving wild species as donors of resistance genes in the breeding process becomes very interesting. Aim of this work was to obtain by simple hybridization interspecific hybrids of flax within the group n = 15 to broaden the genetic variability of the plant and highlight promising original material. Methods. With the purpose of introducing genetic material we included four samples of oil flax Linum humile and wild annual species of flax with the same number of chromosomes Linum angustifolium and Linum bienne. Oil flax was used as the maternal form. Results. Elite plants selected in the F₂ generationhave passed a rigorous selection for the lack of boll dehiscence and for combining morphological features of cultural and wild parents down a number of generations. Promising source material was singled out and studied in detail on such traits as height, number of lateral stems and bolls, weight of thousand seeds, oil content and fatty acid composition of the oil. Conclusions. Promising breeding material was obtained with a combination of complex economically valuable traits – lines A-11 and B-11, which were successfully registered in the National catalogue. Interspecific hybrids that had been obtained became secondary gene pool of wild relatives of Linum humile.